Clinical and Histological Healing after Maxillary Sinus Floor Elevation - Daniele Botticelli (MDPI AG, 2022)
Sinus floor elevation is a surgical procedure that allows for the insertion of the implant in the posterior region of the maxilla in case of insufficient volume of native bone. Several studies have reported a high success rate, and this has helped to spread this surgical procedure around the world. The subject has been extensively studied and this could lead researchers to think that no new scientific evidence can be provided. However, new ideas and discoveries show that research never reaches a conclusion, and that new information can be added all the time. This collection aimed to provide new evidence that could be added to daily clinical work and to provide new ideas for future research.